The Sigma‐2 Receptor/TMEM97 Agonist PB28 Suppresses Cell Proliferation and Invasion by Regulating the PI3K‐AKT‐mTOR Signalling Pathway in Renal Cancer. Issue 24 (16th November 2021) - Zhan, Bo; Zhang, Zhe; Piao, Chiyuan; Dong, Xiao; Du, Yang; Kong, Chuize; Jiang, Yuanjun
Abstract: Sigma‐2 receptor/TMEM97 is overexpressed in many tumours, and sigma‐2 receptor ligands are under investigation for cancer therapy. We intended to evaluate the effect of PB28 on renal cancer in proliferation, migration and invasion in vitro and in vivo. Invasive renal cancer cell lines treated with PB28 (or sigma‐2 receptor antagonist 1) were subjected to cell proliferation, migration and invasion assays. The therapeutic effect of PB28 was performed on nude mice. Western blot for proteins in the PI3K‐AKT‐mTOR signalling pathway was conducted. A CCK‐8 assay was used to examine the effect of the combination of PB28 and cisplatin on renal cancer cells. Significant inhibitory effects were observed on proliferation, migration and invasion of 786‐O and ACHN cells after culturing with PB28. But, the outcomes of sigma‐2 receptor antagonist 1 presented the opposite tendency. PB28 significantly inhibited the proliferative and invasive ability of OS‐RC‐2 cells in vivo. Treatment resulted in decreased phosphorylation of constituents of the PI3K‐AKT‐mTOR pathway. The combination of PB28 and cisplatin showed enhanced efficacy in the inhibition of renal cancer cell proliferation. Taken together, PB28 inhibited the tumorigenic behaviours of renal cancer cells by regulating the PI3K‐AKT‐mTOR signalling pathway and was expected to be a sensitizer of cisplatin.